Majaz Isti'arah (Metaphor) Review of the Word Qiradatan (Ape) in Contemporary Tafsir (Case Study of Ashabus Sabat in Tafsir Quraish Shihab and Tafsir Wahbah Zuhaili) - Luthfi Zainul Muktashi; Andri Nirwana AN; Sufian Suri; Fuadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this research is to find out the meaning of the word qiradatan (ape) which is found in several verses in the Qur'an, whether this word contains the full meaning of ape or just its nature. Researchers examine the meaning of the word qiradatan using contemporary interpretations, namely the Quraish Shihab interpretation and the Wahbah Zuhaili interpretation. The method used in this research is a qualitative method which leads to an explanation of the descriptive analysis model, namely classifying the word